Masculinity and violence in New Mexican Cinema: the Films of Luis Estrada - Puente Vázquez, Claudia Elizabeth (Universidad Pedagógica y Tecnológica de Colombia, 2016)
article seeks to explore the formation of masculinities through their representations in Latin American cinema, specifically in the films of the Mexican director Luis Estrada, a fundamental artist in what has been called New Mexican Film; particularly in his works between 1999 and 2010. Even though the universe of masculinity studies is growing broader each day, its representation in cinema has not been widely explored. This article aims at examining the representation of masculinities and their relation to the representation of the feminine in New Mexican Film, amidst a context of violence, from a feminist critical perspective.